LITERATURE REVIEW: IMPLEMENTASI INTEGRATED MARKETING COMMUNICATION (IMC) DALAM MENUNJANG PEMASARAN RUMAH SAKIT - Ayu Rizki Wachdaniyah; Satriya wijaya; Abdul Hakim Zakkiy Fasya (PROSIDING NATIONAL CONFERENCE FOR UMMAH, 2020)
Marketing communication used by hospitals in an effort to inform and remind consumers directly about the existence of the hospital and the products they offers. Integrated Marketing Communication (IMC) has great potential in influencing business performance, to give hospitals a competitive advantage, to increase brand equity, and to ensure communication effectiveness and consistency by facilitating the achievement of communication and marketing objectives. This literature review aimed to analyze the implementation of IMC elements in supporting hospital marketing. The traditional literature review was used by collecting articles from the google scholar database and the portal garuda. The articles used were publications from 2010 to 2019. Articles that were successfully collected after the screening stages of the two databases were 11 articles. The results show that advertising, personal selling, public relations, direct marketing, and word of mouth activities could support hospital marketing activities. Meanwhile, sales promotion did not have a major effect on hospital marketing activities. Advertising and word of mouth were the most influential elements in hospital marketing efforts. Implementing elements of the IMC has an effect on hospital marketing activities. However, it requires a target and environmental survey, a special budget, and a mature strategy so that messages and information could be conveyed optimally.